An Act for the Better Securing the Government by Disarming Papists and Reputed Papists, 1 W. & M., Sess. 1, ch. 15 (1688) - (:unkn) unknown (My University, 1689)
An Act for the Better Securing the Government by Disarming Papists and Reputed Papists: Prohibition on Catholics from possessing firearms and ammunition unless an oath renouncing their faith was taken.
Keywords: RELIGIOUS RESTRICTION